The influence of extraction method on antioxidant potential of Tilia argentea flowers and bracts - ÇIKLA YILMAZ, DENİZ; AYAZ SEYHAN, SERAP (OVIDIUS UNIV PRESS, 2020)
The objective of this work was to compare the extraction of phenolic compounds from Tilia argentea flowers and bracts by using conventional (solvent extraction) and novel (ultrasound assisted) extraction methods. Ethanol (70 %) extracts were analyzed for their antioxidant activities. Total phenolic content was determined using Folin-Ciocalteu method and the antioxidant potential was determined by DPPH radical scavenging and Ferric Reducing Antioxidant Power (FRAP) assays. To determine the effect of ultrasound treatment on the extraction, same extraction parameters were applied in both methods. The results showed that extracts obtained by ultrasound assisted extraction have higher total phenolic content and antioxidant activity.
Keywords: Tilia argentea; Tilia tomentosa; antioxidant activity; ultrasound assisted extraction; DPPH; FOLIN-CIOCALTEU METHOD; FLAVONOIDS; L.